Public Oversight of Audit Firms: The Slippery Slope of Enforcing Regulation. (8th June 2018) - Dowling, Carlin; Knechel, W. Robert; Moroney, Robyn
Abstract : This study uses the slippery‐slope framework to understand how an oversight regulator's enforcement style influences audit firm compliance. Using data from interviews with audit regulators and audit partners, we find that partners perceive the regulator's enforcement style has shifted from being more collaborative to being more coercive. A consequence of this shift is that partners believe the development of trust between the two parties has been inhibited and a forced compliance climate has emerged. In response, firms have mandated strategies to increase the visibility of compliance, such as increasing mandatory use of checklists. Audit partners express some concern that oversight of the profession has resulted in firms adapting their audit process in ways aimed at minimizing inspection risk and not necessarily improving audit quality.